Implementasi Metode Agile dan Java Server Pages Pada SMS Pooling - Rachmad Hidayat; Lia Andiani; Putri Milanda Bainamus (Jurnal Sistem Informasi dan E-Bisnis, 2025)
This study aims to develop a Java Server Pages (JSP) and MySQL-based SMS Pooling system for PT. Radio Gema Karang Putih Padang uses the Agile Development method. Agile was chosen because of its iterative nature, flexibility to change, and direct user involvement in every stage of development. The research process includes literature study, data collection, sprint planning, gradual development, and functional testing. The research results show that the system is capable of managing incoming and outgoing SMS messages in real-time with stable performance (average reception time of 1.2 seconds, average transmission time of 1.5 seconds). User evaluations revealed high satisfaction levels, with scores of 93% for ease of use, 87% for management speed, 90% for interface design, 95% for developer team response speed, and 92% for feature suitability. These findings indicate that the Agile method is effective in producing a system that is responsive to user needs and ready for further development.   Keywords—java, server, sms, polling, agile